The abbot Giuseppe Venturi’s report that saved the scaliger “bell-clock” of the Gardello’s Tow-er - Matteo Fabris (Studi Veronesi, 2023)
In 1370 a bell was forged to service a public clock in the Scaliger Gardello’s Tower the in Verona; due to its poor acoustic qualities, the bell was moved from the belfry cell onto the top of the tower in 1626. After the sale of the building by the State Property, in 1809, whilst the clock was dismantling, the Abbot Giuseppe Venturi, on behalf of the Ornato municipal Commission, strove with the municipal engineer Giuseppe Barbieri to return unharmed the bell into the heritage of the city. Granted the request, the bell was first showcased in the Frà Giocondo’s Loggia in Piazza dei Signori, and then in the Civic Museum at Palazzo Pompei. After a criticized attempt, in 1872, to restore the bell to its original function, moving it into so-called Pentagona Tower to service the new clock at the Portoni della Bra gifted by Count Antonio Nogarola, it was returned in 1881 to the Civic Museum, and in 1925 moved to the new Castelvecchio Museum, where it is still preserved. Retracing the overall bibliography relating to the artefact, we hereby publish the Abbot Venturi’s report aimed at demonstrating the importance of preserving it. Here he emphasizes the uniqueness of the bell, due to the bizarre peculiarities of realization as well as the Gothic inscriptions and also its memory value of Cansignorio della Scala, Lord of Verona, who had ordered its manufacturing, of the unknown smelter master Jacopo and of what was one of the oldest bell-percussed clocks in Europe.